Negotiation and Agency of Migrant Students within Salafi Muslim Communities in Pekanbaru - Dony Arung Triantoro; Yudhisti Indra Fz; Bifa Fanisa Basri (Jurnal Dakwah Risalah, 2025)
This article analyzes the negotiation practices and agency of Muslim migrant university students in Pekanbaru in response to Salafi power relations. Economic constraints drive many of these migrant students to reside in community-owned mosques, including those managed by groups adhering to Salafi ideology. Building upon this context, the study addresses a central question: how do Muslim migrant university students negotiate their positions and exercise agency when confronted with Salafi power relations in Pekanbaru? This research employs a qualitative method with a narrative approach, with data gathered through in-depth interviews, observation, and documentation. The findings indicate that Muslim migrant university students residing in Salafi-managed mosques do not inherently adopt Salafi religious practices. Instead, they demonstrate the capacity to negotiate and express agency within specific contexts. This strategy enables them to pursue their educational goals while simultaneously securing welfare opportunities during their urban residency. Consequently, this article argues that restrictions on Salafi da’wah activities among Muslim university students are unnecessary, as these students possess the requisite negotiative capacity and agency to navigate such power relations.